Sports promotion strategy for intellectual disabilities by special olympics Indonesia - Purnomo, Eko; Jermaina, Nina; Zainal Abidin, Nor Eeza (Universitas Padjadjaran, 2024)
Background: Disability sports are still not widely known in the wider community. So many people give negative assessments to people with intellectual disabilities. So, there needs to be a promotion to provide education regarding intellectual disabilities and sports (including competitions). Purpose: This research aims to discover how the Bandung Regional Indonesian Special Olympics promotes sports with intellectual disabilities. Methods: This research uses a case study method, with observation, interviews and documentation data collection techniques. This research was conducted in the Indonesian Special Olympics Bandung region and related agencies such as the Youth and Sports Service and the Social Service. Results: This research obtained results that there was cooperation between parties to carry out promotions. Not only organizations, but also the government’s role in providing promotions. The promotion carried out also collaborates with the mass media for reporting, this states that the more news there is, the greater the chance of success in implementing this promotion. And finally, the promotion also uses social media (YouTube, Instagram, Facebook) to target social media users. Conclusion: Implementation of promotions, especially intellectual disabilities, will occur and run successfully if there is cooperation. This collaboration also covers everything from planning to funding. Implications: This research provides implications for implementing disability sports promotion in an unlimited time. This must be done continuously to provide the public with an understanding of intellectual disabilities and sports.